Sistem Pencarian Katalog Buku Menggunakan Hp Dengan Bahasa Pemprograman Java - Dodot Widyantoro; Munifah -; Taufiq Rochman (Performa: Media Ilmiah Teknik Industri, 2013)
New article information regarding the level need of new article books related techniquessupported the technology development in the industry, the student mobility capital ownership and need to design a portable system searches and can be used to access the information on the site new articles more easily. New articles on offer for the easy of accessing the site undertake later expected found information systems can needs the availability information quickly and more. New Articles more is cheap. Seeing the importance of menu dissertations for students and the need for the application to provide convenience and effectiveness students to access it. One of thing to be able to provide ease of application a J2ME, the applied in a mobile phone is mobile has JAVA criteria. Technology is evolving cellular phone founds new articles using technology Java 2 Micro Edition (J2ME) which allows users to create mobile phone java program, the cellular phone supports J2ME Platform. Cellular phone users can perform related books the new media industrial engineering course for later use references in the studied.